1998
DOI: 10.3354/dao032079
|View full text |Cite
|
Sign up to set email alerts
|

Experimental transmission of white spot syndrome virus (WSSV) from black tiger shrimp Penaeus monodon to the sand crab Portunus pelagicus, mud crab Scylla serrata and krill Acetes sp.

Abstract: Whlte spot syndrome virus (WSSV) is the cause of a widespread epizoot~c in cultured shrimp in Thailand and many other countries in Asia. A number of crustacean and other arthropod species have been proposed as reservoirs for the virus by feeding trials and PCR assays. Ho~vever, detailed histological studies are needed to confirm that suspected carriers have active viral infections. This study was carried out to determine whether 3 common crustacean residents of shrimp culture ponds (the sand crab Portunus pela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
69
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 5 publications
1
69
0
Order By: Relevance
“…This latter possibility may be less likely now that WSSV is known to be only distantly related to the baculoviruses (Tsai et al 2000, Liu et al 2001, contrary to the conjecture in earlier publications that it is closely related (e.g., Wongteerasupaya et al 1995). In any case, further studies are necessary to determine the susceptible level to WSSV among haemocyte types, even though haemocytes have been reported to be targets of WSSV in penaeid shrimp (Durand et al 1996, Y. G. Wang et al 1999, C. H. Wang et al 2000 and crabs (Kanchanaphum et al 1998). …”
mentioning
confidence: 38%
See 2 more Smart Citations
“…This latter possibility may be less likely now that WSSV is known to be only distantly related to the baculoviruses (Tsai et al 2000, Liu et al 2001, contrary to the conjecture in earlier publications that it is closely related (e.g., Wongteerasupaya et al 1995). In any case, further studies are necessary to determine the susceptible level to WSSV among haemocyte types, even though haemocytes have been reported to be targets of WSSV in penaeid shrimp (Durand et al 1996, Y. G. Wang et al 1999, C. H. Wang et al 2000 and crabs (Kanchanaphum et al 1998). …”
mentioning
confidence: 38%
“…The virus can be detected by the use of polymerase chain reaction (PCR), in situ hybridisation or monoclonal antibody assays (Kanchanaphum et al 1998, Peng et al 1998, Poulos et al 2001. Thus, in recent years molecular probes have been developed as diagnostic tools and these are already being used for pathogen detection in commercial shrimp farms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the sergestoid shrimp Acetes sp., individuals inoculated by i.m. route had 100% mortality by the 3rd day post inoculation (Supamattaya et al 1998). In contrast, mortality due to WSSV infection was reduced 5-fold when shrimp were inoculated with infected tissues per os, and shrimp mortality occurred over a period of 9 d post feeding.…”
Section: Discussionmentioning
confidence: 93%
“…After the WSSV outbreaks in India during late 1994, in the shrimp culture ponds, several instances of White spots on the exoskeleton of mud crab, S. serrata have been observed. Mud crab has been shown to be a carrier of WSSV in Taiwan and Thailand , Supamattaya et al, 1998. Otta et al (1999) have tested one mud crab with external symptoms and 20 healthy samples without white spots and reported that the one with external symptoms is positive in the 1 st step PCR whereas 3 out of 20 healthy specimens are positive in the 2 nd step PCR indicating that S. serrata is also a carrier of WSSV.…”
Section: Discussion:-mentioning
confidence: 99%